2014
DOI: 10.1016/j.jmoneco.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclicality of credit supply: Firm level evidence

Abstract: Theory predicts that there is a close link between bank credit supply and the evolution of the business cycle. Yet fluctuations in bank-loan supply have been hard to quantify in the timeseries. While loan issuance falls in recessions, it is not clear if this is due to demand or supply. We address this question by studying firms' substitution between bank debt and non-bank debt (public bonds) using firm-level data. Any firm that raises new debt must have a positive demand for external funds. Conditional on issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
221
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(240 citation statements)
references
References 41 publications
16
221
1
2
Order By: Relevance
“…In particular, we assume that if a firm decides to issue debt, then it has to search for creditors. 5 In the analysis below, we assume that creditors appear to firms with constant Poisson arrival rate λ > 0. That is, conditional on searching, the probability of getting financing from new creditors over each time interval [t, t + dt] is λdt and the expected financing lag is 1/λ.…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, we assume that if a firm decides to issue debt, then it has to search for creditors. 5 In the analysis below, we assume that creditors appear to firms with constant Poisson arrival rate λ > 0. That is, conditional on searching, the probability of getting financing from new creditors over each time interval [t, t + dt] is λdt and the expected financing lag is 1/λ.…”
Section: The Modelmentioning
confidence: 99%
“…We respectively denote by A and S the sets of such admissible restructuring and default policies. 5 A growing body of literature argues that assets prices are more sensitive to supply shocks than standard asset pricing theory predicts. Search theory plays a key role in the formulation of models capturing this idea (see e.g.…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher yield loan portfolio has been partially replaced with government bonds and other lower yield securities that can increase portfolio credit quality and increase the volume of liquid assets (Eken et al, 2012) in empirical evidence concluded that banks credit lines where replaced with stronger issued corporate bonds that can be partially explained with sovereign debt crisis of some European countries (Becker and Ivashina, 2014). More than the other participants, small and EURO AREA Croatia USA medium sized companies are exposed to financing shock in credit supply of banking sector without alternative refinance sources and the limits in access to financial markets (Hadeel et al, 2015).…”
Section: Bank Behavior In Economic Cyclesmentioning
confidence: 99%